2010
DOI: 10.1517/14712591003689964
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of glycosylated recombinant human granulocyte colony-stimulating factor (lenograstim) use in current cancer treatment: review of clinical data

Abstract: If usual indications are well defined nowadays, further investigations are still needed to better define optimal use (optimal time to start, treatment duration) and effects on quality of life. In addition, since new strategies for cancer management are emerging, such as oral chemotherapy or targeted therapies, there is a need for clinical data to define lenograstim use in these recent settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…We queried all identified candidate proteins in the Open Targets database 56 to identify repurposing opportunities for COVID-19. While none of the proteins had already been approved drugs or drugs in clinical trials, recombinant human G-CSF (rhG-CSF), such as filgrastim and lenograstim, is used to treat the neutropenia caused by chemotherapy to stimulate the production of granulocytes from the bone marrow 57 . In line with this, phenotypic associations identified in a phenome-wide colocalisation analysis at CSF3 (±500 kb, encoding G-CSF) provided robust evidence for a shared genetic signal between plasma G-CSF and granulocyte and other white blood cell counts 58 , with consistent positive associations across candidate genetic variants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We queried all identified candidate proteins in the Open Targets database 56 to identify repurposing opportunities for COVID-19. While none of the proteins had already been approved drugs or drugs in clinical trials, recombinant human G-CSF (rhG-CSF), such as filgrastim and lenograstim, is used to treat the neutropenia caused by chemotherapy to stimulate the production of granulocytes from the bone marrow 57 . In line with this, phenotypic associations identified in a phenome-wide colocalisation analysis at CSF3 (±500 kb, encoding G-CSF) provided robust evidence for a shared genetic signal between plasma G-CSF and granulocyte and other white blood cell counts 58 , with consistent positive associations across candidate genetic variants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We queried all identified candidate genes in the Open Targets database 45 to identify repurposing opportunities for COVID-19. While none of the genes had already approved drugs or drugs in clinical trials, recombinant human G-CSF (rhG-CSF), such as filgrastim and lenograstim, is used to treat neutropenia caused by chemotherapy to stimulate production of granulocytes from the bone marrow 46 . In line with this, phenotypic associations identified in a phenome-wide analysis of the lead cis-pQTL for G-CSF showed that genetically higher plasma G-CSF was positively associated with granulocyte and other white blood cell counts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason is that the drug prices of the short-acting G-CSFs are quite similar in Taiwan; in addition, a more effective prophylactic benefit of lenograstim was assumed in the model based on the NHIRD analysis. Nevertheless, previous clinical trials have demonstrated that the efficacy of lenograstim in reducing the incidence of FN is similar to that of filgrastim [ 43 ]. In reality, there is generally only one short-acting drug available in a hospital.…”
Section: Discussionmentioning
confidence: 99%